Participación de los padres y rendimiento académico en el área de ciencia y tecnología en estudiantes del primer grado de secundaria de la Institución Educativa N° 60160 del distrito de Fernando Lores 2022 - Soto Urquiza de Paredes, Martha Elizabeth (2024)
It is determined that there is a significant relationship between parental participation and academic performance in the area of Science and Technology in students of the First Grade of Secondary School of Educational Institution No. 60160 of the Fernando Lores district, during the 2022 school year. The research is quantitative, relational, non-experimental, field, correlational and transversal. Applied to a population and sample of 58 students. The students were surveyed using two scaled question questionnaires. It was concluded that: There is a level of parental participation at a medium level of 79.3%, associated with the level of process achieved in terms of the academic performance of first grade secondary school students in the area of Science and Technology. There is a correlation coefficient of 0.722 and a p value of 0.000 and the research hypothesis can be accepted. To raise the level of academic performance of secondary education students of the I.E. No. 60160 of the Fernando Lores district.